Implementasi pembelajaran berdiferensiasi dalam pembelajaran matematika materi bangun ruang balok dan kubus di sekolah dasar - Novia Retno Setiowati; Hasan Mahfud; Anesa Surya; Riyadi Riyadi (Didaktika Dwija Indria, 2024)
This research aims to describe (1) learning planning, (2) implementation of learning, and (3) learning evaluation of differentiated learning in mathematics learning material about blocks and cubes at Angkasa Lanud Adi Soemarmo Elementary School. This research is a type of qualitative descriptive research using a case study method carried out at Angkasa Lanud Adi Soemarmo Elementary School. The subjects in this research is class teachers and class IV students. that totaling students fourteen people. The data collection techniques used in this research is interviews, observation and document study. Test the validity of the data using technical triangulation and data source triangulation. Data analysis using the Creswell model data analysis technique. The results of the research is explain the implementation of differentiated learning in mathematics learning material about building blocks and cubes in class IV at Angkasa Lanud Adi Soemarmo Elementary School has been carried out well starting from learning planning, implementation of learning, and learning evaluation. There is five students who have achieved the learning objectives with an interval of 66-85%, while there is nine students who have achieved the learning objectives with an 86-100% interval. So it can be concluded that all fourteen students at class IV is declared complete because they had achieved the learning objective criteria. The theoretical implication in this research is to increase knowledge regarding the application of differentiated learning in mathematics learning at the elementary school level.